SOURCES OF PREVIOUS ANTI-TUBERCULAR DRUGS EXPOSURE FOR PATIENT REGISTERED IN RNTCP AS RETREATMENT CASES IN DISTRICT ANAND, GUJARAT - Varshney, A M; Singh, U S; Kumar, D (Indian Journal of Community Health, 2013)
Background: M .tuberculosis is an ancient infectious killer that still remains one of the leading causes of death worldwide. India alone accounts for an estimated one fifth of all TB and half of the retreatment TB cases worldwide. Objective: To obtain information regarding treatment practices among retreatment cases of TB patients and to identify socio-demographic factors leading to default or treatment failure or relapse. Methodology: A cross sectional descriptive study was conducted in two TB units of district Anand, Gujarat using pre-tested questionnaire in Gujarati language. A sample size of 100 patients was selected to estimate 50% prevalence of Non-RNTCP treatment with allowable error of 20%. Results: 60% of retreatment cases were of relapse, 37% of participants were of treatment after default, others 9% and 3% of treatment failure cases. 67% of participants received their treatment from Government health facility (RNTCP). Side effects were the commonest reason for defaulting initial treatment. Taking treatment from a private physician was associated with increased risk for side effects as well as defaulting during initial treatment. Socio-demographic factors like age, sex, religion, socio-economic status, occupation were similarly distributed between the default and retreatment groups. Conclusions: Efforts need to be made towards the support, supervision and follow up of the patients in private sector. Patients must be educated about possible adverse drugs and to provide support to overcome them. Reasons for the large number of relapse TB cases from those already treated under the national programme require detailed investigation.